Ethical issues in communication professions : new agendas in communication - Drumwright, Minette E. (New agendas in communication., 2013)
Dynamic, rapid, and radical changes are transforming the communication professions, provoking major implications for ethics. Traditional boundaries blur as media converge; relentless competitive pressures cause some forms of communication to atrophy and permit others to explode; and technological advances occur daily. In this volume, a new generation of scholars take a fresh look at the manner in which ethical issues manifest themselves in their areas of research and suggest new agendas for future research. This book addresses a wide range of questions from a variety of commun.